Cooperation possibility between Gorontalo Government and Foreign Investors regarding the leasing of Saronde Island in North Gorontalo: A public discourse on social media - Tahir, Ismail; Mointi, Siti Nurindah (Privietlab, 2025)
Foreign investment has the potential to develop infrastructure and strengthen local economies. However, clear transparency in governance, environmental sustainability, and equitable benefits for such communities are still questioned. Previous research that examines foreign investment in Indonesian tourism has mainly focused on more established destinations, such as Bali and Lombok whilst only a few is identified about how emerging areas like Saronde Island in Gorontalo could design sustainable investment contracts. This study uses a qualitative analysis from the collected data in social media (Facebook, X, and Instagram) to examine the feasibility and challenges of foreign investment in Saronde Island, Gorontalo. The results indicate that, though foreign investment can boost tourism growth, fragile regulatory and environmental protection frameworks may threaten its sustainability in the longer term period. In comparison with other island tourism destinations, policy innovations, transparent governance, and inclusive stakeholder engagement are decisive factors. Furthermore, this study provides a way forward to the literature of mining investment governance for sustainable investment growth in Indonesia. It also points to significant regulatory and institutional developments necessary to balance economic, environmental, and social accountability. Future studies are encouraged to include primary stakeholder perspectives and investigate hybrid investment models that combine local and foreign investments to guarantee sustainable tourism development in Gorontalo.